The politics of literature in a divided 21st Century - Donn, Katharina (New York, NY : Routledge, 2020)
How does literature matter politically in the 21st century? This book offers an ecocritical framework for exploring the significance of literature today. Featuring a diverse body of texts and authors, it develops a future-oriented politics embedded in those transgressive realities which our political system finds impossible to tame. This book re-imagines political agency, voices, bodies and borders as transformative processes rather than rigid realities, articulating a 'dia-topian' literary politics. Taking a contextual approach, it addresses such urgent global issues as biopolitics, migration and borders, populism, climate change, and terrorism. These readings revitalize fictional worlds for political enquiry, demonstrating how imaginative literature seeds change in a world of closed-off horizons. Prior to the pragmatics of power-play, literary language breathes new energy into the frames of our thought and the shapes of our affects. This book shows how relation, metamorphosis and enmeshment can become salient in a politics beyond the conflict line.
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Politics and literature